2015
DOI: 10.1097/md.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Vaccination Rates in VHA Patients With Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is an inflammatory condition of the digestive tract not caused by infectious agents. Symptoms of IBD, such as diarrhea and pain, diminish one's quality of life. Underlying immune dysregulation may put IBD patients at risk for severe infectious disease making preventative vaccination highly recommended. Therefore, this study sought to assess rates of pneumococcal vaccination in patients with IBD.A cross-sectional observational study was employed utilizing administrative data ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…[ 5 ] A study of 49,350 Veterans Health Administration (VA) patients showed similarly dismal rates of vaccination for pneumovax, with only a 20% rate of vaccination recorded in VA data. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] A study of 49,350 Veterans Health Administration (VA) patients showed similarly dismal rates of vaccination for pneumovax, with only a 20% rate of vaccination recorded in VA data. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated suboptimal rates of vaccination in IBD patients. [ 5 , 6 ] Guidelines for vaccination in IBD patients were published in 2004. [ 7 , 8 ] Despite this, poor vaccination rates persist due to several factors, including lack of awareness on the part of clinicians, fear of potential adverse effects, or ambiguity as to which provider should take responsibility for immunizations.…”
Section: Introductionmentioning
confidence: 99%
“…113 In patients with IBD, a cross-sectional study found lower 1-year mortality rates among adults who were vaccinated compared to those who were not (2.1% vs 4.5%; P < .001). 114 Data from 5 observational studies suggested that pneumococcal vaccine immunogenic response rates in patients with IBD not on immunosuppressive drugs are similar to those seen in the general population. 15,[115][116][117][118] In a case-controlled study, immune response rates were similar between adults with IBD not on immunosuppressive therapy (80%) and agematched healthy controls (85%), but lower in patients on combination immunosuppressive therapy (45%).…”
Section: Pneumococcal Vaccinementioning
confidence: 96%
“…This increased risk is observed even before IBD diagnosis or initiation of immunosuppressive therapy, implicating an underlying immunological change related to the pathogenesis of IBD in the higher risk of IPD [37]. However, 1-year mortality rates were significantly lower among pneumococcal-vaccinated than -unvaccinated IBD patients [38]. The immune response to pneumococcal vaccination in IBD patients is comparable to that of the general population, but immunosuppressive therapy may impair immunogenicity [39,40].…”
Section: Pneumococcal Vaccinementioning
confidence: 98%